Analysis of language errors in student thesis - Nirwana Rasyid; Syahru Ramadan (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2022)
This study aims to describe the forms of spelling errors in the thesis of IAIN Bone students. In addition, it also describes the form of improvement and efforts to reduce language errors. This research is a qualitative descriptive. The subject of this research is the thesis of PGMI Study Program Student, IAIN Bone who graduated in 2020. The free speech technique and note-taking technique were used in collecting research data. Then, the data were analyzed using the Miles and Huberman analysis model which consisted of three stages, namely data reduction, data display, and verification. This study resulted that the spelling errors found in the student's thesis were grouped into three types, namely: a) typographical errors, that included capitalization and italics; b) incorrect use of comma punctuation; and c) word writing errors, which include writing prepositions di- and ke-, non-standard words, affixes di-, word combinations, words with affixes, numbers, and particle -pun. These errors can be reduced by a) providing understanding to students regarding good and correct Indonesian language rules in Indonesian General Courses; b) improving the understanding of the supervisors regarding the rules of the Indonesian language; and c) fostering a positive attitude towards the Indonesian language.